Total Hip Arthroplasty for Crowe Type IV Hip Dysplasia: Surgical Techniques and Postoperative Complications - Xiao‐tong Shi; Chao‐feng Li; Yu Han; Ya Song; Shu‐xuan Li; Jian‐guo Liu (Orthopaedic Surgery, 2019)
Total hip arthroplasty (THA) of Crowe type IV developmental dysplasia of the hip (DDH) is challenging. Although traditional (lateral, posterolateral, and posterior) THA approaches have been used with great anatomic success, they damage periarticular muscles, which are already quite weak in type IV DDH. The recently developed direct anterior approach (DAA) can provide an inter‐nerve and inter‐muscle approach for THA of type IV dysplasia hips. However, femur exposure with the DAA could be difficult during surgery and it is hard to apply femoral shortening osteotomy. THA techniques used for type IV DDH include anatomic hip center techniques (true acetabular reconstruction) and high hip center techniques, wherein an acetabulum is reconstructed above the original one. Although anatomic construction of the hip center is considered “the gold standard” treatment, it is impossible if the anatomical acetabular is too small and shallow. Procedures used to support type IV DDH reduction with anatomic hip center techniques include greater trochanter osteotomy, lesser trochanter osteotomy, and subtrochanteric osteotomy. However, these techniques have yet to be standardized, and it is unclear which is best for type IV DDH. One‐state and two‐state non‐osteotomy reduction techniques have also been introduced to treat type IV DDH. Potential complications of THA performed in patients with type IV DDH include leg length discrepancy (LLD), peri‐operative femur fracture, nonunion of the osteotomy site, and nerve injury. It is worth noting that nowadays an increasing number of Crowe type IV DDH patients are more sensitive to postoperative LLD.